FAO food and nutrition paper; No.41/12: Residues of some veterinary drugs in animals and foods (Deltamethrin, Dihydrostreptomycin, Doramectin, Estradiol-17b, Neomycin, Phoxim, Porcine somatotropins, Progesterone, Streptomycin, Testosterone, Thiamphenicol) - FAO (FAO, 2000)
This book evaluates veterinary drug residues in food. It also provides information on chemical identify, properties, use, pharmacokinetics, metabolism, tissue residue depletion of and analytical methods for the substances indicated on the cover.